Litho-Structural and Metallotectic Context of the Mineralization of the Tondabo Gold Prospect (Brobo, Center of Côte d’Ivoire, West Africa) - Mathurin, DaÏ Bi Seydou; Gbele, Ouattara; Allou, Gnanzou; Barthélémy, Koffi Gnammytchet; Inza, Coulibaly (Current Advances in Geography, Environment and Earth Sciences Vol. 7, 2022)
Rhyodacite and mafic volcanics are the principal hosts of the gold mineralization at the Tondabo prospect, which is located in the northern portion of the Oume-Toumodi-Fettekro greenstone belt (volcanic lavas and volcanoclastites). These rocks underwent a hydrothermal alteration that was characterised by quartz veins and veinlets containing carbonates, sericite, epidote, and sulphide crystals. By silicifying, chloritizing, carbonating, and sericitizing the feldspars, this hydrothermal alteration brought about a ubiquitous alteration of the nearby bodies. Pyrite is prevalent in the metalliferous paragenesis, but pyrrhotite and chalcopyrite are rare. This mineralization suggests that lithological control is present at the Tondabo gold potential. To further understand the features of the Tondabo mineralization, our work combines results from lithostructural analysisand gold analyses. The mineralized deposits are generally affected by a S1 schistosity oriented mainly N000-010\(^{°}\) and minority N040-050\(^{°}\) with a general dip of 60\(^{°}\)- 80\(^{°}\) to the West; however with rare N-S orientations with a dip of 60\(^{°}\)- 80\(^{°}\) to the East. Drilling intervals reveal that the quartz-carbonates veins and veinlets that are found in the highly deformed zones that constitute local shear zones are associated with the highest gold concentrations.